Potential Use and Challenges of Functional Connectivity Mapping in Intractable Epilepsy - Constable, Robert T.; Scheinost, Dustin; Finn, Emily S.; Shen, Xilin; Hampson, Michelle; Winstanley, F. S.; Spencer, Dennis D.; Papademetris, Xenophon (Frontiers in Neurology, 2013)
This review focuses on the use of resting-state functional magnetic resonance imaging data to assess functional connectivity in the human brain for surgical planning in intractable epilepsy. This approach has the potential to predict outcomes for a given surgical procedure based on the pre-surgical functional organization of the brain. Functional connectivity can also identify cortical regions that are organized differently in epilepsy patients either as a direct function of the disease or through indirect compensatory responses. Functional connectivity mapping can also potentially help identify epileptogenic tissue, whether this is a single focal location or a network of seizure-generating tissues and this information can assist in guiding the implantation of electrodes for invasive monitoring. This review covers the basics of connectivity analysis and discusses particular issues associated with analyzing such data. These issues include how to define nodes, as well as differences between connectivity analyses of individual nodes, groups of nodes, and whole-brain assessment at the voxel level. The need for arbitrary thresholds in some connectivity analyses is discussed and a solution to this problem is reviewed. Overall, functional connectivity analysis is becoming an important tool for assessing functional brain organization in surgical planning in epilepsy.